1999
DOI: 10.1093/milmed/164.4.256
|View full text |Cite
|
Sign up to set email alerts
|

Civilian Versus Military Trauma Dogma: Who Do You Trust?

Abstract: Combat trauma differs from its peacetime counterpart by involving a different spectrum of injuries, occurring in austere environments, dealing with mass casualties, and embodying inherent treatment delays. Thus, civilian trauma practices may be inappropriate in certain combat settings. A review of historical as well as current vivilian and military data is presented for four trauma topics (military antishock trousers, wound debridement, colon wounds, fluid resuscitation) in which civilian and military principl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
6
0

Year Published

2003
2003
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(6 citation statements)
references
References 0 publications
0
6
0
Order By: Relevance
“…7,10,17,18 PR in war-related colon injuries report between 25% and 47%. 14,15 Initial data from the current conflict noted a 34% PR rate and a 19% resection and anastomosis rate, although anastomotic failure occurred in 13%. 11 This study found a PA or PR rate of 42%, resection rate of 78%, and failure of PR or PA of 16% with long-term complications in those patients with anastomotic failure.…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…7,10,17,18 PR in war-related colon injuries report between 25% and 47%. 14,15 Initial data from the current conflict noted a 34% PR rate and a 19% resection and anastomosis rate, although anastomotic failure occurred in 13%. 11 This study found a PA or PR rate of 42%, resection rate of 78%, and failure of PR or PA of 16% with long-term complications in those patients with anastomotic failure.…”
Section: Discussionmentioning
confidence: 87%
“…[7][8][9][10][11][12][13][14][15] Military trauma differs from civilian trauma most notably with mechanism and severity of injury, transport to different facilities over large distances with interruptions of care, and triage issues with potential delays in care. Review of civilian and military trauma studies identified disparity in the rate of PR of colon injuries in these settings.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…13,15 Penetrating rectal injuries also have been particularly subject to a dogmatic management approach based mainly on anecdotal and historic data. The age-old dictums of the B3Ds^1 6 of rectal injury treatment-drain, divert, distal washout-along with the previous mandate of stomas for all colorectal injuries has been questioned not only in the civilian literature 17,18 but in recent military conflicts as well. [19][20][21] On the other hand, in Stone and Fabian_s sentinel study advocating primary repair, 48 percent of their prospective patients were excluded, providing doubt as to widespread applicability of their findings.…”
Section: Discussionmentioning
confidence: 99%
“…However, during large-scale accidents, natural or industrial disasters, terrorism acts, or combat operations, a vast number of casualties can develop simultaneously. Such environments present numerous obstacles in providing adequate medical care to the surviving victims including a reduced availability of medical personnel and logistic constraints that limit the volume of available resuscitation fluids (1,3). Therefore, the introduction of an effective pharmacologic therapy for HS that requires small amounts of drug to be administered may considerably increase medical capabilities and improve outcome.…”
mentioning
confidence: 99%